Validation of BEAMS3D against fast-ion D-alpha measurements at ASDEX-Upgrade using FIDASIM - D. Kulla; S. Lazerson; A. Kappatou; M. Weiland; R.C. Wolf; the ASDEX Upgrade Team (Nuclear Fusion)
In this work, we describe validation efforts conducted for the stellarator Monte-Carlo neutral beam and fast ion code BEAMS3D. This code is used at Wendelstein 7-X to analyze fast ion physics and has numerous integrated interfaces facilitating a wide range of applications. We use experimental fast-ion D _α data from the ASDEX Upgrade tokamak, covering on- and off-axis neutral beam heating phases. We obtained synthetic D _α spectra using the FIDASIM code, leveraging a newly developed interface that allows a distribution function from BEAMS3D to be used. Comparing the simulated distributions from BEAMS3D and the well-established NUBEAM codes to the data shows that both codes reproduce the experiment equally well given the same initial conditions. The experimental FIDA spectra are quantitatively matched. The slowing down model of BEAMS3D is thus validated and can be applied to quantitative stellarator investigations in future studies.